1992
DOI: 10.1021/bi00129a022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the phosphoribulokinase sugar phosphate binding domain

Abstract: A recombinant form of Rhodobacter sphaeroides phosphoribulokinase (form I; NADH dependent) has been expressed in and purified to homogeneity from Escherichia coli that harbor the prkA gene in the plasmid pKP1565b. Restriction digestion of the phosphoribulokinase-encoding plasmid produces a tractable 450 bp fragment that encodes amino acid residues 28-179, which include a region (residues 42-54) highly conserved among phosphoribulokinase proteins. Using overlap extension polymerase chain reaction methodology, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
(38 reference statements)
4
32
0
Order By: Relevance
“…On the basis of the structural similarity surrounding the P-loop among these proteins and the locations of conserved amino acids known to be important to catalysis, it is assumed that residues in the vicinity of the P-loop and the bound sulfate molecule form the active site of PRK. Site-directed mutagenesis data are consistent with this conclusion (9)(10)(11). The active site is delineated by the main -sheet, the P-loop that projects into the active site, and the three helices B, E, and F ( Figure 3).…”
Section: Resultssupporting
confidence: 65%
“…On the basis of the structural similarity surrounding the P-loop among these proteins and the locations of conserved amino acids known to be important to catalysis, it is assumed that residues in the vicinity of the P-loop and the bound sulfate molecule form the active site of PRK. Site-directed mutagenesis data are consistent with this conclusion (9)(10)(11). The active site is delineated by the main -sheet, the P-loop that projects into the active site, and the three helices B, E, and F ( Figure 3).…”
Section: Resultssupporting
confidence: 65%
“…While K m effects do not always correlate well with changes in affinity, effects of the type and magnitude observed for R173Q are frequently used to implicate an amino acid in substrate binding (30). The 10 2 -fold effect observed with R173Q is comparable in magnitude to the effect previously reported for R49Q (13). However, it is clear that, if the K m data are interpreted to suggest that R49 and R173 are both involved in binding of Ru5P's C5 phosphoryl group, there would have to be considerable movement of the lid domain to close the active site cavity and bring R49 and R173 into proximity.…”
Section: Discussionmentioning
confidence: 78%
“…While these acidic amino acids could function as activator cation ligands or as a catalytic base, precise assignments of function to each of these residues have not been made. However, a specific function in sugar phosphate substrate binding has been proposed for prokaryotic PRK's R49 (13) or, correspondingly, eukaryotic PRK's R64 (14), on the basis of the large K m Ru5P effects that are observed upon mutagenesis of this arginine.…”
mentioning
confidence: 99%
“…2f; Supplementary Fig. 7b,d)2526272829. Mutagenesis and structural studies on RsPRK have also identified other residues responsible for Ru5P binding (His45 and Lys165) and ATP binding (Arg168).…”
Section: Resultsmentioning
confidence: 96%